Histone Deacetylases as Modulators of the Crosstalk Between Skeletal Muscle and Other Organs - Renzini, Alessandra; D’Onghia, Marco; Coletti, Dario; Moresi, Viviana (Frontiers in Physiology, 2022)
Skeletal muscle plays a major role in controlling body mass and metabolism: it is the most abundant tissue of the body and a major source of humoral factors; in addition, it is primarily responsible for glucose uptake and storage, as well as for protein metabolism. Muscle acts as a metabolic hub, in a crosstalk with other organs and tissues, such as the liver, the brain, and fat tissue. Cytokines, adipokines, and myokines are pivotal mediators of such crosstalk. Many of these circulating factors modulate histone deacetylase (HDAC) expression and/or activity. HDACs form a numerous family of enzymes, divided into four classes based on their homology to their orthologues in yeast. Eleven family members are considered classic HDACs, with a highly conserved deacetylase domain, and fall into Classes I, II, and IV, while class III members are named Sirtuins and are structurally and mechanistically distinct from the members of the other classes. HDACs are key regulators of skeletal muscle metabolism, both in physiological conditions and following metabolic stress, participating in the highly dynamic adaptative responses of the muscle to external stimuli. In turn, HDAC expression and activity are closely regulated by the metabolic demands of the skeletal muscle. For instance, NAD+ levels link Class III (Sirtuin) enzymatic activity to the energy status of the cell, and starvation or exercise affect Class II HDAC stability and intracellular localization. SUMOylation or phosphorylation of Class II HDACs are modulated by circulating factors, thus establishing a bidirectional link between HDAC activity and endocrine, paracrine, and autocrine factors. Indeed, besides being targets of adipo-myokines, HDACs affect the synthesis of myokines by skeletal muscle, altering the composition of the humoral milieu and ultimately contributing to the muscle functioning as an endocrine organ. In this review, we discuss recent findings on the interplay between HDACs and circulating factors, in relation to skeletal muscle metabolism and its adaptative response to energy demand. We believe that enhancing knowledge on the specific functions of HDACs may have clinical implications leading to the use of improved HDAC inhibitors for the treatment of metabolic syndromes or aging.